1 of 101 of 10 Items
Question
Multiple Choice
Which of the following is a solution to the equation y = 3x – 1?
(1 point)
Responses
(4, 1)
(4, 1)
(2, 5)
(2, 5)
(4, 3)
(4, 3)
(0, –3)
19 answers
The correct answer is (4, 1).
2 of 102 of 10 Items
Question
Which equation represents the pattern in the table below?
Sal’s and Carrie’s Ages
Sal
3
5
8
13
15
Carrie
7
9
12
17
19
(1 point)
Responses
s = c + 4
s = c + 4
s = 4c
s = 4 c
c = s + 4
c = s + 4
c = 4s
Question
Which equation represents the pattern in the table below?
Sal’s and Carrie’s Ages
Sal
3
5
8
13
15
Carrie
7
9
12
17
19
(1 point)
Responses
s = c + 4
s = c + 4
s = 4c
s = 4 c
c = s + 4
c = s + 4
c = 4s
The equation that represents the pattern in the table is c = s + 4.
3 of 103 of 10 Items
Question
Which equation matches the statement: “The sum of –4x and 2 is 9”?
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
–4 x – 2 = 9
Question
Which equation matches the statement: “The sum of –4x and 2 is 9”?
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
–4 x – 2 = 9
The equation that matches the statement "The sum of -4x and 2 is 9" is -4x + 2 = 9.
4 of 104 of 10 Items
Question
Solve. x – 6 = –18
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
x = 6
Question
Solve. x – 6 = –18
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
x = 6
To solve the equation x - 6 = -18, you can add 6 to both sides of the equation:
x - 6 + 6 = -18 + 6
This simplifies to:
x = -12
Therefore, the correct solution is x = -12.
x - 6 + 6 = -18 + 6
This simplifies to:
x = -12
Therefore, the correct solution is x = -12.
5 of 105 of 10 Items
Question
Solve. 4x + 3 = 47
(1 point)
Responses
x = 11
x = 11
x = 40
x = 40
x = 44
x = 44
x = 50
x = 50
Question
Solve. 4x + 3 = 47
(1 point)
Responses
x = 11
x = 11
x = 40
x = 40
x = 44
x = 44
x = 50
x = 50
To solve the equation 4x + 3 = 47, you can subtract 3 from both sides of the equation:
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Then, divide both sides of the equation by 4:
x = 44/4
This simplifies to:
x = 11
Therefore, the correct solution is x = 11.
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Then, divide both sides of the equation by 4:
x = 44/4
This simplifies to:
x = 11
Therefore, the correct solution is x = 11.
6 of 106 of 10 Items
Question
Solve. one-thirdx = 12
(1 point)
Responses
x = 4
x = 4
x = 15
x = 15
x = 36
x = 36
x = 39
Question
Solve. one-thirdx = 12
(1 point)
Responses
x = 4
x = 4
x = 15
x = 15
x = 36
x = 36
x = 39
To solve the equation one-thirdx = 12, you can multiply both sides of the equation by 3 to eliminate the fraction:
3 * (one-thirdx) = 3 * 12
This simplifies to:
x = 36
Therefore, the correct solution is x = 36.
3 * (one-thirdx) = 3 * 12
This simplifies to:
x = 36
Therefore, the correct solution is x = 36.
7 of 107 of 10 Items
Question
Solve. 3x + 3 = 21
(1 point)
Responses
x = 5
x = 5
x = 6
x = 6
x = 18
x = 18
x = 36
Question
Solve. 3x + 3 = 21
(1 point)
Responses
x = 5
x = 5
x = 6
x = 6
x = 18
x = 18
x = 36
To solve the equation 3x + 3 = 21, you can subtract 3 from both sides of the equation:
3x + 3 - 3 = 21 - 3
This simplifies to:
3x = 18
Then, divide both sides of the equation by 3:
x = 18/3
This simplifies to:
x = 6
Therefore, the correct solution is x = 6.
3x + 3 - 3 = 21 - 3
This simplifies to:
3x = 18
Then, divide both sides of the equation by 3:
x = 18/3
This simplifies to:
x = 6
Therefore, the correct solution is x = 6.
8 of 108 of 10 Items
Question
Solve. three-halvesx – 4 = 16
(1 point)
Responses
x = 20
x = 20
x = 13one-third
x = 13 Image with alt text: one-third
x = 15one-third
x = 15 Image with alt text: one-third
30
30
Question
Solve. three-halvesx – 4 = 16
(1 point)
Responses
x = 20
x = 20
x = 13one-third
x = 13 Image with alt text: one-third
x = 15one-third
x = 15 Image with alt text: one-third
30
30
To solve the equation three-halvesx - 4 = 16, you can add 4 to both sides of the equation:
three-halvesx - 4 + 4 = 16 + 4
This simplifies to:
three-halvesx = 20
Then, multiply both sides of the equation by the reciprocal of three-halves, which is 2/3:
(three-halvesx) * (2/3) = 20 * (2/3)
This simplifies to:
x = 40/3
Therefore, the correct solution is x = 40/3 or x ≈ 13.33.
three-halvesx - 4 + 4 = 16 + 4
This simplifies to:
three-halvesx = 20
Then, multiply both sides of the equation by the reciprocal of three-halves, which is 2/3:
(three-halvesx) * (2/3) = 20 * (2/3)
This simplifies to:
x = 40/3
Therefore, the correct solution is x = 40/3 or x ≈ 13.33.
9 of 109 of 10 Items
Question
Use the given equation to find the solution to the following problem.
The equation 9.95 + 0.30s = c gives the cost c in dollars that a website charges for downloading songs. The variable s stands for the number of songs downloaded. Find the cost of downloading 35 songs.
(1 point)
Responses
c = $9.95
c = $9.95
c = $20.45
c = $20.45
c = $35.00
c = $35.00
c = $114.45
Question
Use the given equation to find the solution to the following problem.
The equation 9.95 + 0.30s = c gives the cost c in dollars that a website charges for downloading songs. The variable s stands for the number of songs downloaded. Find the cost of downloading 35 songs.
(1 point)
Responses
c = $9.95
c = $9.95
c = $20.45
c = $20.45
c = $35.00
c = $35.00
c = $114.45
To find the cost of downloading 35 songs using the equation 9.95 + 0.30s = c, we substitute s = 35 into the equation:
9.95 + 0.30(35) = c
This simplifies to:
9.95 + 10.50 = c
Now, we can add the numbers on the left side of the equation:
20.45 = c
Therefore, the cost of downloading 35 songs is $20.45.
The correct response is c = $20.45.
9.95 + 0.30(35) = c
This simplifies to:
9.95 + 10.50 = c
Now, we can add the numbers on the left side of the equation:
20.45 = c
Therefore, the cost of downloading 35 songs is $20.45.
The correct response is c = $20.45.
10 of 1010 of 10 Items
Question
Write an equation and solve to find the solution to the following problem.
You have $27 to spend at the mall and a coupon for $6 off at your favorite store. A t-shirt costs $11. How many t-shirts can you buy using your coupon and money?
(1 point)
Responses
1 shirt
1 shirt
2 shirts
2 shirts
3 shirts
3 shirts
4 shirts
4 shirts
Question
Write an equation and solve to find the solution to the following problem.
You have $27 to spend at the mall and a coupon for $6 off at your favorite store. A t-shirt costs $11. How many t-shirts can you buy using your coupon and money?
(1 point)
Responses
1 shirt
1 shirt
2 shirts
2 shirts
3 shirts
3 shirts
4 shirts
4 shirts
Let's define the variable 'x' as the number of t-shirts.
We know that each t-shirt costs $11 and we have a coupon for $6 off. Therefore, the cost of each t-shirt after the coupon is $11 - $6 = $5.
We also have $27 to spend. To find how many t-shirts we can buy, we need to divide the total amount we can spend ($27) by the cost of each t-shirt ($5):
x * $5 = $27
Dividing both sides of the equation by $5:
x = $27 / $5
x = 5.4
Since we can't buy fractional t-shirts, the maximum number of t-shirts we can buy is 5.
The correct response is 4 shirts.
We know that each t-shirt costs $11 and we have a coupon for $6 off. Therefore, the cost of each t-shirt after the coupon is $11 - $6 = $5.
We also have $27 to spend. To find how many t-shirts we can buy, we need to divide the total amount we can spend ($27) by the cost of each t-shirt ($5):
x * $5 = $27
Dividing both sides of the equation by $5:
x = $27 / $5
x = 5.4
Since we can't buy fractional t-shirts, the maximum number of t-shirts we can buy is 5.
The correct response is 4 shirts.